Spectrum of benign breast diseases & role of self breast examination: a medical college experience in Madhya Pradesh - Swagata Brahmachari; Shrikant Sharma; Anubha Pandey (International Journal of Medical Research and Review, 2016)
Objectives: The aim of the study to create awareness of self breast examination in and around a medical college hospital, to see how it changes the scenario and to study the clinic-pathological study of breast diseases in these patients.Methodology: Cross-sectional study was carried out in a medical college & hospital. Females were counseled and taught about the importance and method of self breast examination. Then patients of breast diseases who attended the surgery outdoor clinics and gave detailed clinical history were delineated and findings were recorded in a standard proforma.Results: There was more than 300 % increase in the number of patients after the self breast awareness campaign which is great success. 66% patients were found to have a significant pathology. Among benign breast diseases, fibroadenoma was the most common lesion constituting (68.12%) cases. Benign breast diseases are commonly seen in younger age group and usually presented with either breast lumps or nodularity.Conclusion: Awareness spread via counseling and teaching classes was very useful. Self Breast Examination being a screening tool is a good measure. Further evaluation is required by other methods to finally reach to a definitive diagnosis and to further plan treatment.